Hydrofluorocarbon nanoparticles for 19F MRI-fluorescence dual imaging and chemo-photodynamic therapy. Issue 6 (24th January 2022) - Wu, Tingjuan; Chen, Kexin; Jiang, Mou; Li, Anfeng; Peng, Xingxing; Chen, Shizhen; Yang, Zhigang; Zhou, Xin; Zheng, Xing; Jiang, Zhong-Xing
Abstract : The higher co-solubility of functional agents enables the sensitive 19 F MRI-fluorescence dual imaging and synergistic PTT, PDT and chemotherapy to overcome tumor hypoxia. Abstract : The synergistic chemotherapy and photodynamic therapy (PDT) may significantly improve the cancer therapeutic efficacy, in which fluorinated nanoemulsions are highly advantageous for their ability to deliver oxygen to hypoxic tumors and provide fluorine-19 magnetic resonance imaging ( 19 F MRI). The low solubility of chemotherapy drugs and photosensitizers in current perfluorocarbon (PFC)-based 19 F MRI agents usually leads to complicated formulations or chemical modifications and low nanoemulsion stability and performance. Herein, we employ readily available partially fluorinated ethyl 2-(3, 5-bis(trifluoromethyl)phenyl)acetate as the 19 F MRI agent and the solvent to dissolve the cancer stem cell inhibitor salinomycin and the photosensitizer ICG for the convenient preparation of 19 F MRI-fluorescence dual imaging and synergistic chemotherapy, photothermal and photodynamic therapy nanoemulsions. The chemotherapy drug salinomycin has a high solubility in the partially fluorinated reagent, facilitating its high loading and efficient delivery. Paramagnetic iron(iii ) (Fe 3+ ) is incorporated into the nanoemulsion through the dissolved chelator to significantly improve the 19 F MRI sensitivity. Furthermore, the dissolved fluorinated 2-pyridone enables the efficient capture and sustained release of singlet oxygen in the dark for high PDT efficacy. The multifunctional nanoemulsions show sensitive 19 F MRI and fluorescence dual imaging capability and high synergistic chemotherapy, photothermal and photodynamic therapy efficacy in cancer cells, which may be valuable oxygen delivery, sustained ROS generating and release, dual imaging and multimodal therapy agents for hypoxic tumors. This study provided a convenient co-solubilization strategy for the rapid construction of multifunctional theranostics for hypoxic tumors.